2021
DOI: 10.15244/pjoes/121514
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antioxidant and Antimicrobial Compounds of Volatiles from Leaves, Stems and Flowers of Olives

Abstract: Introduction Tunisia is the main olive producing country in the southern Mediterranean. 34% of its cultivated land is devoted to olive growing, which extends from the north to the south of the country. This sector plays, economic, social and environmental roles, contributing to food security, job creation, equilibrium of the commercial balance, preservation of natural resources and limitation of the rural exodus. The olive forest is dominated by the oil cultivars, Chemlali in the center and south of the countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In addition, the abundance of these triterpenes in the adsorbates increased compared with CL (global control), from around 30% for uvaol in CL to 50% in SS adsorbate (SS ads). The enrichment of this kind of pentacyclic triterpenes is significant considering their potential anti-inflammatory, antioxidant, and cardioprotective bioactivities, among others [12,[61][62][63]. α-tocopherol is another compound of interest not only for its recognized antioxidant capacity but also for its ability to transport target compounds with bioactive potential through neuronal cells [64].…”
Section: Figurementioning
confidence: 99%
“…In addition, the abundance of these triterpenes in the adsorbates increased compared with CL (global control), from around 30% for uvaol in CL to 50% in SS adsorbate (SS ads). The enrichment of this kind of pentacyclic triterpenes is significant considering their potential anti-inflammatory, antioxidant, and cardioprotective bioactivities, among others [12,[61][62][63]. α-tocopherol is another compound of interest not only for its recognized antioxidant capacity but also for its ability to transport target compounds with bioactive potential through neuronal cells [64].…”
Section: Figurementioning
confidence: 99%
“…Numerous publications about the study of olive extracts have been published recently, albeit these studies focus mostly on the volatile components because of their antioxidant activity (Naija et al, 2021). Beyond the leaves and the oil, a thorough evaluation of the various extraction techniques for the many olive tree materials was lacking.…”
Section: State Of Artmentioning
confidence: 99%
“…Many phytochemicals are known firstly for their powerful antioxidant capacity to cope thermal, drought and oxidative stress, secondly for their antifungal activity against pathogenic fungi for several species [18-25, 52, 53]. In this context, Saidana et al [53] suggested that volatiles might be an eventual source of alternative antimicrobial and antioxidant agents interesting for potential use in the biological control. These results encourage us to promote them in the agronomic sector.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%